Willy Brandt - Viola, Tom (New York Chelsea House Publishers, 1988)
A biography of the German leader who served as mayor of West Berlin, chairman of the Social Democratic Party, and chancellor of West Germany.
Keywords: Brandt, Willy -- 1913-1992 -- Juvenile literature; Brandt, Willy -- 1913-1992.; Heads of state -- Juvenile literature. -- Germany (West) -- Biography; Heads of state; Germany (West) -- Politics and government -- Juvenile literature